Icariin promotes functional recovery in rats after spinal cord injury by inhibiting YAP and regulating PPM1B ubiquitination to inhibiting the activation of reactive astrocytes - Sa Feng; Sa Feng; Linyan Liu; Linyan Liu; Yuelin Cheng; Yuelin Cheng; Mengmeng Zhou; Mengmeng Zhou; Haoqiang Zhu; Haoqiang Zhu; Xinyan Zhao; Xinyan Zhao; et al. (Frontiers Media S.A., 2024)
ObjectiveThe limited ability to regenerate axons after spinal cord injury (SCI) is influenced by factors such as astrocyte activation, reactive proliferation, and glial scar formation. The TGF-β/Smad (transforming growth factor-β/mothers against decapentaplegic homolog) pathway, associated with astrocytic scarring, plays a crucial role in recovery post-injury. This study aims to investigate how icariin (ICA) interacts with reactive astrocytes in the treatment of spinal cord injury.MethodsA rat SCI model was constructed, and the recovery of motor function was observed after treatment with ICA.HE staining, LFB staining, immunofluorescence staining, and Western blotting were employed to assess ICA's ability to inhibit astrocyte proliferation in rats following spinal cord injury by modulating YAP, as well as to evaluate the reparative effects of ICA on the injured spinal cord tissue. Primary astrocytes were isolated and cultured. Immunoprecipitation-Western Blot (IP-WB) ubiquitination and cytoplasm-nuclear separation were employed to assess PPM1B ubiquitination and nuclear translocation.ResultsThe CatWalk XT gait analysis, BBB (Basso, Beattie, and Bresnahan) score, electrophysiological measurements, HE staining, and LFB staining collectively demonstrated that ICA promotes motor function and tissue recovery following spinal cord injury in rats. Immunofluorescence staining and Western Blot analyses revealed that ICA inhibits astrocyte proliferation in rats post-spinal cord injury by suppressing YAP activity. Furthermore, the activation of YAP by XMU-MP-1 was shown to compromise the efficacy of ICA in these rats after spinal cord injury. Additional immunofluorescence staining and Western Blot experiments confirmed that ICA inhibits TGFβ1-induced astrocyte activation through the regulation of YAP. The knockdown of PPM1B (protein phosphatase, Mg2+/Mn2+-dependent 1B) in astrocytes was found to inhibit TGFβ signaling. Additionally, YAP was shown to regulate PPM1B ubiquitination and nuclear translocation through immunoprecipitation-Western blot analysis, along with the segregation of cytoplasm and nucleus.ConclusionIcariin promotes functional recovery in rats after spinal cord injury by inhibiting YAP and regulating PPM1B ubiquitination to inhibiting the activation of reactive astrocytes.